PENINGKATAN KEMAMPUAN BAHASA MADURA MELALUI METODE BERNYANYI LAGU MADURA PADA ANAK USIA 5–6 TAHUN DI TK BAROKATUL ULUM - Siti Aisyah Tarido; Ratnasari Dwi Ade Chandra; Rizki Sevi Triana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The present study was motivated by the phenomenon of declining regional language proficiency among younger generations. Preliminary data collected at TK Barokatul Ulum revealed that 85% of Group B students were unable to use Madurese vocabulary productively during learning activities. This study aimed to examine the effectiveness of a singing method utilizing Ronjengan, a culturally based local song, as a strategy to enhance the language competence of children aged 5–6 years while simultaneously contributing to the preservation of local cultural heritage. Methodologically, the research employed the Classroom Action Research framework developed by Kemmis and McTaggart, consisting of two cycles that included the stages of planning, action, observation, and reflection. The participants comprised 18 children from Group B. Data were collected through methodological triangulation involving observation, interviews, and documentation, and were analyzed using a descriptive qualitative approach. The intervention demonstrated a substantial improvement trajectory throughout the research process. Learning mastery at the pre-cycle stage was only 15%, increasing to 50% after Cycle I and reaching 77.8% by the end of Cycle II, thereby exceeding the predetermined success criterion of 75%. These findings confirm that the implementation of Madurese songs as a learning medium is effective in improving children's mastery of the regional language while simultaneously fostering the internalization of local wisdom values from an early stage of development. ABSTRAK Fenomena memudarnya kompetensi berbahasa daerah pada generasi muda melatarbelakangi kajian ini, di mana data awal di TK Barokatul Ulum menunjukkan 85% peserta didik kelompok B belum mampu menggunakan kosakata Bahasa Madura secara produktif dalam pembelajaran. Penelitian ini bertujuan mengeksplorasi efektivitas metode bernyanyi berbasis lagu bermuatan budaya lokal Ronjengan sebagai strategi peningkatan kompetensi kebahasaan anak usia 5–6 tahun sekaligus upaya pelestarian kearifan lokal. Secara metodologis, penelitian mengadopsi kerangka Penelitian Tindakan Kelas model Kemmis dan McTaggart yang terdiri atas dua siklus dengan tahapan perencanaan, tindakan, observasi, dan refleksi. Partisipan penelitian melibatkan 18 anak kelompok B, sementara pengumpulan data dilakukan melalui triangulasi teknik berupa observasi, wawancara, dan dokumentasi yang dianalisis secara deskriptif kualitatif. Trajektori peningkatan yang signifikan teridentifikasi sepanjang proses intervensi. Ketuntasan belajar pada fase pra-siklus hanya mencapai 15%, meningkat menjadi 50% pasca-Siklus I, dan mencapai 77,8% pada akhir Siklus II melampaui indikator keberhasilan 75%. Hasil ini mengonfirmasi bahwa penerapan lagu Madura sebagai medium pembelajaran terbukti efektif dalam meningkatkan penguasaan bahasa daerah sekaligus menginternalisasikan nilai-nilai kearifan lokal sejak tahap perkembangan awal anak.